Rumah Cerdas Mandiri (RCM): Program Edukasi Berkelanjutan Wilayah Nginden Jangkungan Surabaya - Lindiawati; Laila Saleh Marta; Tatik Suryani (JURNAL DAYA-MAS, 2021)
Nginden Jangungan Village, which is located in Sukolilo sub-district, Surabaya, has an area with low socioeconomic conditions whis is contrast to its surroundings of good private universities, expensive housing area, shopping block2, hotels, luxurious places of worship, and an international hospital. Thus, this area with poor conditions is like a poverty within the metropolitan of Surabaya. For people living in this poor area contrasting condition with its modern surroundings has made them think that they are inferior compared to their superior surroundings. Therefore, as early as possible, the younger generation of this group, must be equiped with proper education making them able and confident that they can be successful in the future. Therefore, it is deemed necessary to provide extra learning activities for children, namely learning assistance for the National Examination subjects, as well as efforts to increase children's self-confidence which is monitored using Behavior Check List (BCL). All of these activities are carried out in a program called Rumah Cerdas Mandiri (RCM) which is located in one of the RW halls in the Nginden Jangkungan Village, Surabaya. The result of this RCM program is that the academic ability of children is improving well although there is some of them that need to be improved. In addition, based on the results of the BCL analysis, it shows that children have self-confidence, courage to express themselves and increased curiosity. These two direct outputs are very important as a trigger for their future success